2020
DOI: 10.1371/journal.pone.0223941
|View full text |Cite|
|
Sign up to set email alerts
|

Pupil diameter differentiates expertise in dental radiography visual search

Abstract: Expert behavior is characterized by rapid information processing abilities, dependent on more structured schemata in long-term memory designated for their domain-specific tasks. From this understanding, expertise can effectively reduce cognitive load on a domain-specific task. However, certain tasks could still evoke different gradations of load even for an expert, e.g., when having to detect subtle anomalies in dental radiographs. Our aim was to measure pupil diameter response to anomalies of varying levels o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Furthermore, Castner et al (2020) reported that data loss values produced by manufacturer software are not always reliable. They found that for a participant with a reported tracking ratio of 98% (a data loss of 2%), an additional large gap in the left eye gaze signal-approximately 3.5s out of a 90s recording-appeared as data loss, but was labelled as a blink.…”
Section: Data Loss and Interpolationmentioning
confidence: 99%
“…Furthermore, Castner et al (2020) reported that data loss values produced by manufacturer software are not always reliable. They found that for a participant with a reported tracking ratio of 98% (a data loss of 2%), an additional large gap in the left eye gaze signal-approximately 3.5s out of a 90s recording-appeared as data loss, but was labelled as a blink.…”
Section: Data Loss and Interpolationmentioning
confidence: 99%
“…Di-Flumeri et al assessed, in real-time, the vigilance level of an Air Traffic Controller by measuring the time-to-first fixation as an indicator of a high level of vigilance [ 9 ]. Consequently, there seems to be a difference in gaze depending on the workload [ 10 ], and the experience of individuals. This difference in visual perception according to expertise is now well established.…”
Section: Introductionmentioning
confidence: 99%
“…Pupil diameter has also successfully been used to detect cognitive load in a variety of scenarios, including driving [39], during low visual load tasks [40], route planning with maps [41], and simultaneous interpreting [42]. Furthermore, it was successfully used to differentiate expertise closely related to cognitive load [43] We applied preprocessing steps to improve data quality of the pupil signal. First, we removed periods that were marked as blinks, as well as the 100ms right before and after a blink.…”
Section: Pupil-related Featuresmentioning
confidence: 99%